Microcontact Printing of Cholinergic Neurons in Organotypic Brain Slices - Steiner, Katharina; Humpel, Christian (Frontiers in Neurology, 2021)
Alzheimer's disease is a severe neurodegenerative disorder of the brain, characterized by beta-amyloid plaques, tau pathology, and cell death of cholinergic neurons, resulting in loss of memory. The reasons for the damage of the cholinergic neurons are not clear, but the nerve growth factor (NGF) is the most potent trophic factor to support the survival of these neurons. In the present study we aim to microprint NGF onto semipermeable 0.4 μm pore membranes and couple them with organotypic brain slices of the basal nucleus of Meynert and to characterize neuronal survival and axonal growth. The brain slices were prepared from postnatal day 10 wildtype mice (C57BL6), cultured on membranes for 2–6 weeks, stained, and characterized for choline acetyltransferase (ChAT). The NGF was microcontact printed in 28 lines, each with 35 μm width, 35 μm space between them, and with a length of 8 mm. As NGF alone could not be printed on the membranes, NGF was embedded into collagen hydrogels and the brain slices were placed at the center of the microprints and the cholinergic neurons that survived. The ChAT+ processes were found to grow along with the NGF microcontact prints, but cells also migrated. Within the brain slices, some form of re-organization along the NGF microcontact prints occurred, especially the glial fibrillary acidic protein (GFAP)+ astrocytes. In conclusion, we provided a novel innovative microcontact printing technique on semipermeable membranes which can be coupled with brain slices. Collagen was used as a loading substance and allowed the microcontact printing of nearly any protein of interest.